PERANCANANGAN APLIKASI PENGENALAN ALAT KESENIAN PATINGTUNG BERBASIS ANDROID - Ahmad Dedi; Radi Radi (Teknik Informatika Fakultas Ilmu Komputer, 2018)
Abstrak Patingtung art is one of the arts in Banten, this art is usually held at the time of harvesting rice. At present Patingtung art is very rare and no one even uses it anymore. Patingtung art as one of the cultural riches that is almost extinct requires a way for the art to be known by the public. The tools used in this art have rarely been found and expertise in vocal fields is difficult to find. To solve this problem in this study a simulation of multimedia-based patingtung art tools was made so that this art could be recognized by the public.